THE SHORTEST PATH PROBLEM SOLVING WITH TIME WINDOW FOR PERISHABLE PRODUCTS - KARTIKA (NIM: 23410038); Pembimbing : Suprayogi, Ph.D, WINANDA
According to Graf theory, the shortest path determination is a problem of looking for a path between two vertices in a weighted graph to obtain the minimum amount of weight. Therefore, the determination of the shortest path problem also called optimization problem for determining the trajectory of the point of origin to point of destination by minimizing costs. Several algorithms have been developed in solving this problem. Each algorithm has a different way of solving a particular problem. In this study, carried out the development of algorithms to determine the critical path from origin point to destination point on a network for the delivery of products that have deterioration and limited time window to minimize the total cost and the selection of vehicles that will be used for solving the problem. The Algorithm that developed is Dijkstra's algorithm. The first stages of development the algorithm is to modify the network of the problem study. Network modification is done by making the network replication. The second stage is to make problem-solving steps to minimize the total cost, consists of a fixed cost of the vehicle, variable cost of the vehicle, vehicle turnover costs, deterioration cost and parking fees with modified Dijkstra algorithm. Dijkstra modifications made since the problems studied can not be modeled mathematically. To test the developed algorithm, we used hypothetical data. Numerical examples in this study were the determination of the shortest path with time window and the determination of the shortest path without time window with a non-linear deterioration function.